PENGARUH SOSIALISASI SAK EMKM, PERSEPSI PELAKU UMKM DAN PEMAHAMAN AKUNTANSI TERHADAP PENERAPAN SAK EMKM PADA KELOMPOK UPPKA (USAHA PENINGKATAN PENDAPATAN KELUARGA AKSEPTOR) DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA KOTA PALEMBANG - Syahabia Ayu Ramadhani; Feronika Rosalin; Ahmad Fikriyansyah; Wandestarido Wandestarido (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this study is to ascertain how the UPPKA DPPKB group applies SAK EMKM in relation to their perceptions about MSME players, accounting knowledge, and SAK EMKM socialization characteristics. Primary data from respondents' questionnaires are used in this study. Seventy respondents made up the saturated sample that was used for this investigation. This study employed a quantitative methodology with descriptive verification data analysis. The application of SAK EMKM in the UPPKA Group of the Palembang City Population Control and Family Planning Office is not significantly impacted by the socialization of SAK EMKM, according to partial test results, but it is significantly impacted positively by MSME actors' perceptions and accounting knowledge. The findings of the simultaneous tests indicate that the implementation of SAK EMKM is influenced by at least one of the independent variables, which are socialization, views of MSME actors, and accounting knowledge. Only a small portion of the variation in the application of SAK EMKM can be explained by the variables of socialization, perception, and accounting understanding, as indicated by the coefficient of determination of 23.2%. The majority of the variation is likely caused by other factors not included in the study, possibly including non-linear patterns between the independent and dependent variables. Keyword: SAK EMKM Socialization, MSME Actor Perceptions, Accounting Understanding, and SAK EMKM Implementation